IDENTIFYING REGIONAL DIVERSIFICATION AND SPATIAL DEPENDENCE OF EMPLOYMENT IN EU REGIONS AS ONE OF SOCIAL COHESION INDICATORS - Bal-Domańska, Beata (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
The objective of this article is to identify spatial dependence in terms of employment as one of the basic indicators of social and economic cohesion in the European Union. The implementation of the social cohesion principle refers to reducing disproportions between countries and regions in areas such as employment. For the European Community, this aspect is of particular importance since one of its objectives consists precisely in the promotion of the development of balanced economic activities across the territory.The presented analysis is to provide an answer to the question about the occurrence of regional clusters characterised by similar labour market development levels. This approach can be helpful in taking decisions about financial support and allow for the identification of spatial clusters characterised by an unfavourable situation. The analysis covers the period 2005-2012, which allowed for the assessment of changes in spatial interaction vis-à-vis employment as one of the most important indicators of social cohesion after EU enlargement in 2004 – the largest single expansion of the European Union (EU) in terms of territory, number of states and population, including labour market.